Instilling values of javanese leadership culture for primary school principal - Jumintono, Siti Supeni, Dian Esti Nurati, Feri Faila Sufa, (Opción, 2019)
The purpose of this study is to understand and know the views of the Principals in applying the values of Javanese cultural leadership Ki Hajar Dewantara. The research method uses approaches: historical, anthropological, and hermeneutic, with participant observation, in-depth interviews, and documentation. As a result, there are similarities and differences of views by the principal towards the values of Javanese cultural leadership. In conclusion, school programs, management of artifacts, vision and mission are policy implications by the principal.